P2GS Web-Based E-CRM with WhatsApp API for MSME Customer Engagement - Alia Akhmad, Khabib; Nurohman (BEST, 2025)
This study discusses the development, implementation, and user guide of the web-based Electronic Customer Relationship Management (E-CRM) P2GS system integrated with the WhatsApp API as an innovative solution for customer relationship management in Micro, Small, and Medium Enterprises (MSMEs). The system was developed using the System Development Life Cycle (SDLC) Waterfall model, comprising requirement analysis, design, implementation, testing, and evaluation stages. The trial was conducted on five MSMEs that are members of Perkumpulan Pengusaha Gading Sukowati (P2GS) in Sragen. Key features include a dashboard, sales management, purchase management, product master data, stock-taking, reporting, and store settings. The WhatsApp API integration enables automated messaging to customers, enhancing retention and engagement. Evaluation results indicate a 23% increase in customer retention, an 18% reduction in marketing costs, and a 12% increase in monthly revenue. The system’s usage is documented in the P2GS E-CRM Application User Guide to facilitate adoption and training. This study demonstrates that integrating popular technologies into E-CRM systems can significantly improve efficiency and performance in MSMEs